The Social and Psychological Effects of Inclusive Education of Persons with Hearing Disability in Society: A Field Study at the Disability Resource Centre (Sharjah University) - Nagwa Babiker Abdalla Yousif (MDPI AG, 2021)
The objective of inclusive education is to increase the quality of social and psychological integration in society of students with disabilities in the learning process. This study aimed to identify the social and psychological effects of inclusive education of students with hearing disabilities at Sharjah University’s Disability Resource Centre. The study adopted a descriptive analytical approach with a purposive sample comprising 24 students with hearing impairment. An electronic questionnaire comprising 25 psychological and social statements and nine open-ended questions was administered to collect quantitative and qualitative data. The results revealed positive correlation coefficients between inclusive education and both psychological adjustment and social interaction and negative relationships between gender and age and both social interaction and psychological adaptation variables (for age ρ = 0.091 and ρ = 0.262 and for gender ρ = 0.47 and ρ = 0.076, respectively). A statistically significant difference of less than 0.05 was found in favour of those who agreed that inclusion affects psychological adaptation. A statistically significant difference of less than 0.05 was found in favour of students who agreed that inclusion affects social interaction. The research results can be used in the practice of inclusive education to determine ways to improve the social and psychological adaptation of students with hearing impairments.